2019
DOI: 10.1186/s12944-019-1054-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics coupled with pathway analysis characterizes serum metabolic changes in response to potassium oxonate induced hyperuricemic rats

Abstract: Background Hyperuricemia as a metabolic disease is usually associated with lipid metabolic disorder. The purpose of this study is to identify potential lipid biomarkers and provide the evidence for the relationship between hyperuricemia and lipid-related diseases. Methods Lipidomics-a specialized study of lipid metabolites-has become a highly sensitive and powerful tool for biomarker discovery. In this work, an ultra-performance liquid chromatography-quadruole-time-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The metabolites involved in glycerophospholipid metabolism and sphingolipid metabolism account for a large proportion of all metabolites, prompting attention to the correlation between abnormal lipid metabolism and HUA. In the previous study of HUA rat model by potassium oxonate or fructose in our laboratory [ 25 , 40 ], glycerophospholipid metabolism was implicated. A large number of glycerophospholipids and their metabolites in serum samples of HUA patients were disturbed; phospholipid metabolism disorder occurred; PC, LysoPC, PE, LysoPE, PI, LysoPI, PS, PG, PGP, and LysoPA were mainly involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites involved in glycerophospholipid metabolism and sphingolipid metabolism account for a large proportion of all metabolites, prompting attention to the correlation between abnormal lipid metabolism and HUA. In the previous study of HUA rat model by potassium oxonate or fructose in our laboratory [ 25 , 40 ], glycerophospholipid metabolism was implicated. A large number of glycerophospholipids and their metabolites in serum samples of HUA patients were disturbed; phospholipid metabolism disorder occurred; PC, LysoPC, PE, LysoPE, PI, LysoPI, PS, PG, PGP, and LysoPA were mainly involved.…”
Section: Discussionmentioning
confidence: 99%
“…e study of metabolic disorders is meant for assisting disease, clinical diagnosis, screening of therapeutic drugs and targets [18][19][20]. Over recent years, extensive studies have been extensively conducted on HUA metabolomics, but these studies were mainly focused on animal experiments and there is little research describing HUA metabolic disorders in humans [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of PLA2 and LPCAT3 activity results in accelerated glycerophospholipid metabolism, so the levels of PC and LPC were both up-regulated in HUA rats. In our previous studies, PEs are key biomarkers of potassium oxonate induced HUA rats [ 57 ]. Interestingly, we also found that PE(18:3/22:4) and PE(24:1/24:1) are the key biomarkers in the treatment of HUA with Plantaginis Semen this time.…”
Section: Discussionmentioning
confidence: 99%
“…If sufficient carbohydrates are not available, the body begins to metabolize fats into ketone bodies ( β -hydroxybutyrate and acetoacetate) to provide the necessary fuel. Lipidomics studies revealed that saturated fatty acid LPCs were upregulated and unsaturated fatty acid LPCs were downregulated in potassium oxonate-induced hyperuricemic rats [ 31 ], while increased levels of all PCs and unsaturated fatty acid LPCs together with decreased levels of saturated fatty acid LPCs were detected in rats with hyperuricemia induced by fructose [ 32 ]. These contrary conclusions might be due to different model-making methods.…”
Section: Discussionmentioning
confidence: 99%